2015
DOI: 10.2174/1568026615666150317221549
|View full text |Cite
|
Sign up to set email alerts
|

(6-Bromo-1,4-dimethyl-9<i>H</i>-carbazol-3-yl-methylene)-hydrazine (Carbhydraz) Acts as a GPER Agonist in Breast Cancer Cells

Abstract: Estrogens control a wide number of aspects of human physiology and play a key role in multiple diseases, including cancer. Estrogens act by binding to and activating the cognate receptor (ER), however numerous studies have revealed that the G protein-coupled receptor named GPR30/GPER mediates also estrogen signals. As ER and GPER share the ability to bind to same compounds, the use of GPER-selective ligands has allowed a better understanding of the biological responses mediated by GPER. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Of note, GPER expression has been associated with negative clinical features and poor survival rates in patients with hormone-sensitive tumors ( Filardo et al, 2006 ; Smith et al, 2009 , 2007 ; Sjöström et al, 2014 ), suggesting that GPER might be involved in the stimulatory action exerted by estrogens in these malignancies. Considering that GPER and ER bind promiscuously to many compounds, including endogenous and environmental estrogens as well as antiestrogens ( Lappano et al, 2012a ; Prossnitz and Barton, 2011 ), an ongoing major challenge in dissecting the transduction network mediated by GPER is the discovery of novel agents able to act selectively through this receptor, although certain ligands have been identified in our and other previous studies ( Bologa et al, 2006 ; Dennis et al, 2009 , 2011 ; Lappano et al, 2012b ; Maggiolini et al, 2015 ; Sinicropi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 84%
“…Of note, GPER expression has been associated with negative clinical features and poor survival rates in patients with hormone-sensitive tumors ( Filardo et al, 2006 ; Smith et al, 2009 , 2007 ; Sjöström et al, 2014 ), suggesting that GPER might be involved in the stimulatory action exerted by estrogens in these malignancies. Considering that GPER and ER bind promiscuously to many compounds, including endogenous and environmental estrogens as well as antiestrogens ( Lappano et al, 2012a ; Prossnitz and Barton, 2011 ), an ongoing major challenge in dissecting the transduction network mediated by GPER is the discovery of novel agents able to act selectively through this receptor, although certain ligands have been identified in our and other previous studies ( Bologa et al, 2006 ; Dennis et al, 2009 , 2011 ; Lappano et al, 2012b ; Maggiolini et al, 2015 ; Sinicropi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 84%
“…These two moieties, which were named GPER-L1 and GPER-L2, demonstrated the ability to act as GPER agonists without any affinity for ER. Furthermore, a derivative of the carbazole moiety, named carbhydraz, has been recently synthesized and characterized toward its stimulatory activity through GPER (35). To date, only a molecule exhibited inhibitory properties toward both GPER and ER.…”
Section: Endogenous and Exogenous Gper Ligand Binding Modesmentioning
confidence: 99%
“…Using the aforementioned approaches, several different natural and synthetic ligands of GPER (Fig. 1) have been identified along with their binding modes as resulting from docking simulations (13,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the interaction with DNA or its metabolizing enzymes that induce programmed cell death, namely apoptosis . Several carbazole analogues structurally derived from ellipticine, an alkaloid from Ochrosia elliptica labill, introduced for the treatment of metastatic breast cancer, but later dismissed because of poor aqueous solubility and severe side effects, were synthesized …”
Section: Introductionmentioning
confidence: 99%
“…Trimethoxyphenylurea 1,4‐dimethylcarbazoles, N ‐thioalkylcarbazoles, 1,4‐dimethyl‐ N ‐alkylcarbazoles, N ‐(1,4‐dimethyl‐9 H ‐carbazol‐3‐yl)‐ N′ ‐alkylguanidines, benzofuro[2,3‐ f ]quinazolin‐1(2 H )‐ones, and hydrazine‐carbazole derivatives were also prepared, and some of them showed interesting anti‐proliferative activity against breast cancer cells without affecting the viability of non‐tumor cell lines. Several studies have reported that carbazole derivatives, such as ellipticine and celiptium (Figure ), are inhibitors of human topoisomerases I and II …”
Section: Introductionmentioning
confidence: 99%